2009
DOI: 10.3945/ajcn.2008.27073
|View full text |Cite
|
Sign up to set email alerts
|

Generation of epidermal growth factor–expressing Lactococcus lactis and its enhancement on intestinal development and growth of early-weaned mice

Abstract: This study showed that EGF-LL had beneficial effects on the intestinal growth of newly weaned mice. The combination of growth factor delivery and a probiotic approach may offer possibilities for formulating dietary supplements for children during their weaning transition stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 46 publications
3
54
1
Order By: Relevance
“…Herein, we demonstrate that an intervention to reduce the CVA does not improve body weight; therefore, the intestinal changes may indicate the existence of altered epithelial cell proliferation in the CF condition or may reflect a tissue response to bacteria (29), which are overgrown in the CF intestine (30,31). rhIGFBP-3 treatment, as it decreased CVA length and muscle thickness, may be beneficial in ameliorating the intestinal propensity to develop mucous plugs, given the increased numbers of goblet cells in the distended villus and the decreased motility in the CF intestine (32).…”
Section: Discussionmentioning
confidence: 84%
“…Herein, we demonstrate that an intervention to reduce the CVA does not improve body weight; therefore, the intestinal changes may indicate the existence of altered epithelial cell proliferation in the CF condition or may reflect a tissue response to bacteria (29), which are overgrown in the CF intestine (30,31). rhIGFBP-3 treatment, as it decreased CVA length and muscle thickness, may be beneficial in ameliorating the intestinal propensity to develop mucous plugs, given the increased numbers of goblet cells in the distended villus and the decreased motility in the CF intestine (32).…”
Section: Discussionmentioning
confidence: 84%
“…Porcine EGF expressing L. lactis was generated via a recombinant approach as previously described (Cheung et al, 2009). Briefly, the mature EGF sequence was amplified from porcine RNA then ligated into an expression vector which was transformed into L. lactis.…”
Section: Production Of Recombinant Egf Using L Lactismentioning
confidence: 99%
“…We have previously generated a strain of porcine EGF producing Lactococcus lactis (EGF-LL) (Cheung et al, 2009), and demonstrated that supplementation of early-weaned piglets with this recombinant EGF increases body weight gain and gain to feed ratio (Bedford et al, 2014). The current study sought to further understand the in vivo mechanisms behind the improved growth and intestinal development observed with EGF containing culture supernatant through the investigation of the dynamic changes of potential key genes involved, jejunal enzyme activity, as well as histomorphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor is an important factor which associates with the proliferation and differentiation of enterocyte, hence the stimulation of EGF introduces to villous growth [2]. Platelet-derived growth factor A is also an important factor which associates with the formation of villous structure [6].…”
mentioning
confidence: 99%